Lucha contra el despotismo: Guerras civiles, republicanismo clásico y orientalismo en Ecuador (1858-1883) - Espinosa Fernández de Córdova, Carlos (Jahrbuch für Geschichte Lateinamerikas, 2021)
The article examines the political discourses employed by conservatives in two cases of civil war in nineteenth-century Ecuador, the Crisis of 1858-1860 and the Restoration of 1882-1883. In both cases, conservatives drew on the vocabulary of classical republicanism to establish a contrast between the sovereign people or the nation and an oppressive tyranny. Thus, references to ancient Roman dictators or emperors were prevalent. Alternatively, the binary opposition between an enslaved people seeking to free themselves from an oppressive tyrant could also be couched in orientalist terms, as opposition to a sultan and his janissary corps. Such a construction of the political field delegitimated the regime in power and allowed for the establishment of a broad coalition to unseat it. In addition, the article explores how the political actors in the context of these intrastate conflicts conceived the social fact of civil war and the role of external actors who intervened in the conflicts.